2005
DOI: 10.1074/jbc.m509082200
|View full text |Cite
|
Sign up to set email alerts
|

Domain Unfolding Plays a Role in Superfibronectin Formation

Abstract: Superfibronectin (sFN) is a fibronectin (FN) aggregate that is formed by mixing FN with anastellin, a fragment of the first type III domain of FN. However, the mechanism of this aggregation has not been clear. In this study, we found that anastellin co-precipitated with FN in a ratio of ϳ4:1, anastellin:FN monomer. The primary binding site for anastellin was in the segment III 1-3, which bound three molecules of anastellin and was able to form a precipitate without the rest of the FN molecule. Anastellin bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(110 citation statements)
references
References 53 publications
6
103
1
Order By: Relevance
“…Anastellin binds FN to form a large aggregate, called superFN, which has FN matrix-like fibrillar structures when observed by light microscopy. Our previous studies indicated that the opening or unfolding of FNIII domains is important for anastellin binding and aggregation (24,37). We also found that the N-terminal FN fragment, I 1-9, which prevented FN matrix formation in cell culture, did not inhibit superFN aggregation.…”
Section: Fibronectin (Fn)mentioning
confidence: 66%
See 2 more Smart Citations
“…Anastellin binds FN to form a large aggregate, called superFN, which has FN matrix-like fibrillar structures when observed by light microscopy. Our previous studies indicated that the opening or unfolding of FNIII domains is important for anastellin binding and aggregation (24,37). We also found that the N-terminal FN fragment, I 1-9, which prevented FN matrix formation in cell culture, did not inhibit superFN aggregation.…”
Section: Fibronectin (Fn)mentioning
confidence: 66%
“…III [7][8][9][10] and the variable domain seem to play roles as integrin binding sites. III 4 -5, III 12-14, and I 10 -12 have contradictory reports (24,26,30), so they may only be required for particular cell types or under some conditions. On the other hand, many studies consistently show that I 1-9 is crucial for FN matrix assembly.…”
Section: Fibronectin (Fn)mentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that these domains are actually folded, as indicated by tryptophan fluorescence, but are transiently unfolding and refolding. We previously suggested that domains III-1, III-2, III-3, and III-11 transiently open and bind anastellin, a fragment of domain III-1, when forming the in vitro induced FN matrix known as superfibronectin (18,19). We suggest that the FN-III domains (n ϭ 3).…”
Section: Discussionmentioning
confidence: 99%
“…In cell-assembled fibrils, the pulling speed is nearly zero, so it is difficult to extrapolate the cell-applied force that would be needed to unfold these domains. In addition to mechanical unfolding of FN-III domains, transient opening of certain FN-III domains has been demonstrated in the absence of applied force during the assembly of in vitro assembled super-fibronectin (18,19).The second theory to explain fibril elasticity contends that FN molecules are in a compact conformation in relaxed fibrils and are stretched to the extended conformation in elongated fibrils (see Fig. 1A, mechanism 1) (20).…”
mentioning
confidence: 99%